2015
DOI: 10.1186/1471-2369-16-4
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury among adult patients with sepsis in a low-income country: clinical patterns and short-term outcomes

Abstract: BackgroundAcute kidney injury (AKI) is a common complication of sepsis. We determined the prevalence of AKI among adult patients with sepsis on the medical wards in a low-income country and described their clinical pattern and outcomes at discharge.MethodsWe conducted a cross-sectional study of sepsis-related AKI on the adult medical wards of Mulago National Referral Hospital between January and April 2013. All patients meeting the American College of Chest Physicians (ACP) sepsis criteria were recruited. Demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
41
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 14 publications
6
41
0
1
Order By: Relevance
“…15 Two studies from India have shown that the AKI incidence in inpatient wards and pediatric intensive care units ranged between 5%-9% and 25%-36%, respectively. 11,12 In a recent study from the largest hospital in Uganda, the AKI prevalence among patients admitted with sepsis was 16%, and the hospital mortality was 21% for patients with septic AKI. 10 The cause of AKI can be broadly categorized as hospital acquired and community acquired (Table 1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 Two studies from India have shown that the AKI incidence in inpatient wards and pediatric intensive care units ranged between 5%-9% and 25%-36%, respectively. 11,12 In a recent study from the largest hospital in Uganda, the AKI prevalence among patients admitted with sepsis was 16%, and the hospital mortality was 21% for patients with septic AKI. 10 The cause of AKI can be broadly categorized as hospital acquired and community acquired (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…9,10 On the other hand, AKI commonly occurs in the community in less-developed nations. 11 However, in this article, it is difficult to define the incidence of AKI, since no nationwide disease registries exist and data are usually derived from single-center experiences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of properly trained professionals aware of the problem may delay the detection and referral to specialized services, leading to worse results (1)(2)(3)(4)(5)(6)(7)(8) .…”
Section: Introductionmentioning
confidence: 99%
“…It may be present in the community and in hospital settings. Sepsis is the most common cause of AKI in critical patients and is associated with higher severity, increasing risk of death and hospital admissions, compared to non-septic patients (2) . In intensive care units (ICU), its incidence may reach 20%, and 49% to 70% of patients need dialytic treatment (3)(4) .…”
Section: Introductionmentioning
confidence: 99%